In vivo imaging of chronic active lesions in multiple sclerosis. (April 2022) - Calvi, Alberto; Haider, Lukas; Prados, Ferran; Tur, Carmen; Chard, Declan; Barkhof, Frederik
New clinical activity in multiple sclerosis (MS) is often accompanied by acute inflammation which subsides. However, there is growing evidence that a substantial proportion of lesions remain active well beyond the acute phase. Chronic active lesions are most frequently found in progressive MS and are characterised by a border of inflammation associated with iron-enriched cells, leading to ongoing tissue injury. Identifying imaging markers for chronic active lesions in vivo are thus a major research goal. We reviewed the literature on imaging of chronic active lesion in MS, focussing on 'slowly expanding lesions' (SELs), detected by volumetric longitudinal magnetic resonance imaging (MRI) and 'rim-positive' lesions, identified by susceptibility iron-sensitive MRI. Both SELs and rim-positive lesions have been found to be prognostically relevant to future disability. Little is known about the co-occurrence of rims around SELs and their inter-relationship with other emerging techniques such as dynamic contrast enhancement (DCE) and positron emission tomography (PET).